Development Of Retail Trade in Uzbekistan - Safarov Bakhtiyor Djurakulovich (Zien Journals, 2022)
The article provides a statistical analysis of the dynamics of retail trade in Uzbekistan. The Global Retail Trade Development Index identifies key strategic directions for the countries with the highest ratings. A SWOT analysis of retail trade and its situation in Uzbekistan was conducted. Recommendations for the use of Omnichannel, ROPO, and SHOP-IN-SHOP in the development of retail trade
Keywords: trade; retail trade; competitiveness; retail sales